Relationship between speed ability and endurance ability of freestyle swimming speed - Suandi Selian; Henni aryunita; Dodi Irwansyah (Universitas Suryakancana, 2024)
Someone who competes in a swimming sport surely will take a distance, therefore a swimmer to reach that distance will involve physical factors namely endurance and speed so that the swimmer is able to swim with maximum speed and endurance. This study is conducted by survey methods with a correlation analysis technique that connects the three independent variables to the dependent variable so that this study has no control over the treatment as well as no change in research. Based on the results of the testing of the first hypothesis, it shows that there is a positive relationship between speed ability and endurance ability of the freestyle swimming speed of the male athlete in Tirta Prima Medan